3.x – 28 = x + 36 (12)^2 . x = 56 + 10.13x Làm hộ em vs ạ, em cảm ơn

3.x – 28 = x + 36
(12)^2 . x = 56 + 10.13x
Làm hộ em vs ạ, em cảm ơn

2 bình luận về “3.x – 28 = x + 36 (12)^2 . x = 56 + 10.13x Làm hộ em vs ạ, em cảm ơn”

  1. 3x – 28 = x + 36
    3x – x = 36 + 28
    2x = 64
    x = 64 : 2
    x = 32
    ____________________________
    (12^2)x = 56 + 10.13x
    144x = 56 + 130x
    144x – 130x = 56
    14x = 56
    x = 56 : 14
    x = 4
    _____
     #Na

    Trả lời
  2. 3x-28=x+36
    => 3x-28-x-36=0
    => (3x-x)-(28+36)=0
    => 2x-64=0
    => 2x=64
    => x=32
    Vậy x=32
    12^2 .x=56+10.13x
    => 144x=56+130x
    => 144x-130x-56=0
    => 14x-56=0
    => 14x=56
    => x=4
    Vậy x=4

    Trả lời

Viết một bình luận

Câu hỏi mới